Art "identity" of a poetic work in "female" and "male" epistolary (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article the ways of organization of poetic text are considered at lexico-semantic level which appears as it «formal identity». The author analyzes features of male and female style which form models of the male and female writing. The modern poetry acts as an object and a subject of studying.
Keywords: male and female writing; identity